Restricting the view and connecting the dots: Dangers of a web search engine monopoly - Narayanan, Kulathuramaiyer; Balke, Wolf-Tilo (Journal of Universal Computer Science, 2006)
Everyone realizes how powerful the few big Web search engine companies have become, both in terms of financial resources due to soaring stock quotes and in terms of the still hidden value of the wealth of information available to them. Following the common belief that “information is power” the implications of what the data collection of a de-facto monopolist in the field like Google could be used for should be obvious. However, user studies show that the real implications of what a company like Google can do, is already ...